Environmental Public Interest Litigation in Romania: Recent Developments in Domestic Courts and the Implications of the CJEU Judgment in Case C-252/22 .......... 213 - Ionescu, Diana (Fundamental Rights and Climate Change: Exploring New Perspectives and Corresponding Remedies, 2025)
Access to justice in environmental cases is an essential guarantee of the substantive right to a healthy environment. Nevertheless, the legal rules and their interpretation differ greatly. The Romanian legal framework on judicial review in environmental cases is focused on the private interest requirement. However, using the purposive method of statutory interpretation aimed at protecting the constitutional right to a healthy environment, the Cluj Court of Appeal, a court of appeal in the Western part of Romania, acknowledged that every person has the right to initiate public interest litigation in environmental cases. This judicial transition from the doctrine of the individual private interest to the objective criteria of protecting the law and collective rights specific to the environmental public interest was, however, blocked by the decision of another court of appeal and the CJEU judgment in case C-252/22. In this judgment, ruling on a preliminary reference submitted in a case first decided by the Cluj Court of Appeal, the CJEU decided that, as a rule, private interest is a legitimate requirement under Article 9 (3) of the Aarhus Convention. In this perspective, environmental non-governmental organizations are the only claimants who have the power to represent the public interest. Even if the CJEU promoted a restrictive interpretation of public interest under Article 9 (3), the Opinion of AG Laila Medina opened the way to a new perspective: the thesis that public interest litigation can be initiated not only by NGOs but also by individuals or other associations that genuinely want to protect the environment.